2006
DOI: 10.1021/ac0521495
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Microfabricated Probes for Combined Atomic Force and High-Resolution Scanning Electrochemical Microscopy

Abstract: A combined atomic force and scanning electrochemical microscope probe is presented. The probe is electrically insulated except at the very apex of the tip, which has a radius of curvature in the range of 10-15 nm. Steady-state cyclic voltammetry measurements for the reduction of Ru(NH3)6Cl3 and feedback experiments showed a distinct and reproducible response of the electrode. These experimental results agreed with finite element simulations for the corresponding diffusion process. Sequentially topographical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 44 publications
1
67
0
Order By: Relevance
“…In this fascinating situation it will be possible to directly correlate protein partitioning with the modification of their activity. In this context the activity of AFM cantilevers and tips modification in order to make them able to measure ion currents in solution already started (Menozzi et al, 2005;Gullo et al, 2006). AFM applied in the force spectroscopy mode to membrane proteins will also increase our knowledge about the intra and inter-molecular interactions of these proteins which are relevant to drive protein folding, oligomerization and functional activity (Janovjak et al, 2008).…”
Section: Conclusion and Future Trendsmentioning
confidence: 99%
“…In this fascinating situation it will be possible to directly correlate protein partitioning with the modification of their activity. In this context the activity of AFM cantilevers and tips modification in order to make them able to measure ion currents in solution already started (Menozzi et al, 2005;Gullo et al, 2006). AFM applied in the force spectroscopy mode to membrane proteins will also increase our knowledge about the intra and inter-molecular interactions of these proteins which are relevant to drive protein folding, oligomerization and functional activity (Janovjak et al, 2008).…”
Section: Conclusion and Future Trendsmentioning
confidence: 99%
“…Transmission electron microscope (TEM) images revealed that tips with such a well pronounce hysteresis showed also an important gap between the electrode and the insulation at the apex. Theoretical modeling confirmed that this gap was responsible for the hysteresis [4]; it acted like a reservoir of ions, which could only be refreshed by slow diffusion through the narrow opening at the tip apex.…”
Section: Nanotools For Biologymentioning
confidence: 89%
“…It was important to realize that when operating such a probe in a buffer solution one actually conducts an electrochemical experiment [4]. Therefore it was essential, that these probes were first characterized by cyclic voltamograms and electrochemical feedback measurements and second, that the future, routinely performed biological experiments are also to be conducted at the correct potentials under potentiostatic control [5].…”
Section: Nanotools For Biologymentioning
confidence: 99%
“…Thus, several groups have developed a combined AFM-SECM method which represents a significant advance in SPM methodology. [14,[17][18][19][20][21][22][23][24][25][26][27][28] Indeed, AFM gives high-resolution topographic information and is able to precisely control the distance between the sample and the probe, whereas SECM can provide detailed information on local anodic or cathodic processes. Thus, electrochemical images can be analyzed with full know-A C H T U N G T R E N N U N G ledge of the corresponding surface topography.…”
Section: Introductionmentioning
confidence: 99%